BS36 Reduced insulin-like growth factor-1 receptor expression enhances vascular repair and regeneration in whole body insulin resistance. (May 2019) - Walker, Andrew; Sengupta, Anshu; Patel, Peysh; Ali, Noman; Mercer, Ben; Slater, Thomas; Drozd, Michael; Watt, Nicole; Yuldasheva, Nadira; Paradine, Katherine; Warmke, Nele; Kearney, Mark; et al.
Abstract : Introduction: Insulin resistance is an independent risk factor for cardiovascular disease. We have previously shown that the insulin-like growth factor-1 receptor (IGF-1R) is a negative regulator of insulin receptor (IR) signalling, by sequestering IR subunits in insulin resistant IR:IGF1R 'hybrid receptors'. By crossing IR haploinsufficient (IRKO) mice with IGF-1R haploinsufficient (IGF-1RKO) mice (producing "double knockout" or DKO mice), we have previously demonstrated rescue of the endothelial dysfunction caused by insulin resistance. Whether this is associated with wider benefits in vascular biology is unclear. Our original hypothesis is that reduced expression of the IGF-1R in whole body insulin resistance improves vascular repair and regeneration. Methods: Metabolic assessment included measurement of weight gain and glucose and insulin tolerance testing. Denuding femoral artery endothelial injury was induced with angioplasty guidewire and repair was quantified by Evans Blue perfusion 4 days later. For hindlimb ischemia, the left femoral artery was ligated and excised, with sham surgery contralaterally. Control:ischemic limb perfusion ratio was assessed with weekly laser Doppler imaging for 4 weeks. Data are expressed as mean (standard error) and compared using t-tests; * denotes p<0.05; ns = not significant. Results: Glucose and insulin tolerance tests were similar in DKO and IRKO mice. Body weight was significantly lower in DKO than IRKO [area under curve (arbitrary units) 116(2.1) Vs 123(2.4)* n=15]. DKO had a significantly greater proportion of recovered endothelium (Figure 1 A&B) after denuding wire injury to the femoral artery compared with IRKO [0.55 (0.04) Vs 0.46 (0.02) p=0.047*, n=8-14]. ]. DKO had superior recovery (Figure 2 A&B) after induction of hindlimb ischemia [area under curve limb perfusion ratio (arbitrary units) 2.2(0.11) Vs 1.3(0.08)* n=12-19]. Conclusion: Reduced IGF-1R expression improves vascular repair and regeneration in the context of whole-body insulin resistance. Further work will aim to elucidate the possible mechanisms for these novel observations. Conflict of interest: None